Effects of auditory enrichment and regular human contact on stress response, underlying fearfulness, and growth performance in broiler chickens - Mohd Tamagi, H.; Idrus, Z.; Farjam, A. Soleimani; Awad, E.Atta; Hussein, A.Nabilah (Verlag Eugen Ulmer, Stuttgart, 2024)
A study determined whether providing auditory enrichment to broiler chickens with or without regular human contact influenced stress response, underlying fearfulness, and growth performance. The experiment was conducted in a completely randomised design with a 3 × 2 factorial arrangement consisting of three auditory enrichment (AE) treatments and two human contact (HC) regimens. From days 1 to 35, a total of 480 day-old male broiler chicks were allotted to one of the three auditory enrichment treatments: no auditory enrichment (NE), auditory enrichment with classical music (Vivaldi's Four Season) (ME), or auditory enrichment with Quran recitation (Yaseen chapter) (QE). An equal number of chicks from each AE treatment were subjected to either no-human contact (NC) or regular human contact (the experimenter placed her right hand into the cage for 30 seconds twice daily) (RC). On day 7, the ME birds had significantly higher body weights (BW) than the control and QE birds. The BW of the QE chicks was significantly lower than that of their ME counterparts on day 14. HC had a negligible influence on the birds' BW, feed intake (FI), or feed conversion ratio (FCR). Neither AE nor HC significantly affected tonic immobility (TI) duration or number of induction attempts. ME and QE significantly affected serum levels of corticosterone (CORT) on days 14 and 21. However, HC did not affect CORT. In conclusion, ME has a beneficial effect on the performance of broilers during the early stage of growth. Exposure to ME or QE dampens stress response but not underlying fearfulness in chickens at market age.